Frequency of Urinary Tract Infection among Children Presenting with Acute Febrile Illness - Abid Imran, Fatima Batool, Abed Al Rahman Al Midaka, Farhana Shaheen, Sumera Kanwal, Said Jamal Shah, Qazi Maaz, Ansar Hussain, Adil Farooq, Waseem Javed, Jawaria Javed, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Acute febrile illnesses are common in children worldwide, especially in those under 5 years of age. Febrile illness is typically presumptively treated as malaria in African children in endemic areas, where the majority of these children are given anti-malarial drugs. This study will provide us the latest and updated information regarding urinary tract infections among children presenting with acute febrile illness in our population. Objective: The objective of this study is to evaluate the frequency of urinary tract infections among children presenting with acute febrile illness. Although much research has already been conducted on this topic, no recent study has been done in our population. This study will provide us with the latest and updated information regarding urinary tract infections among children presenting with acute febrile illness in our population. The aim to evaluate the frequency of urinary tract infections in children with acute febrile illness presenting at a tertiary care hospital, in Peshawar. Methods: A total of 250 children meeting the inclusion criteria were enrolled from Hayatabad Medical Complex, Peshawar during December 2021 to December 2022. Clean-catch urine samples were collected, and UTI was diagnosed based on the presence of ≥105 colony-forming units (CFU) per milliliter of a single uropathogenic on urine culture. Demographic data, clinical features, and laboratory investigations (complete blood count, C-reactive protein, urinalysis) were recorded. Potential risk factors for UTI, such as age, gender, antibiotic use, and underlying medical conditions, were analyzed using appropriate statistical tests (chi-square test, logistic regression). The sample was 250 keeping a 20.3% proportion of UTI among febrile children 95% confidence interval and 5% margin of error using the WHO sample size estimation formula. Results: The results show that among 162 children Mean age was 22 months with SD ± 12.08. 100(62%) children were male and 62(38%) children were female. 23(14%) children had urinary tract infection and 139(86%) children didn’t had urinary tract infection. Conclusions: The study found a 14% frequency of UTI among children with acute febrile illness presenting at a tertiary care hospital in Peshawar, Pakistan. These findings highlight the need for routine urine screening and appropriate management of UTI in the evaluation of febrile illnesses in children in this setting. Keywords: Urinary tract infection, children acute febrile illness.